The '24' Effect: How entertainment media affects the public perception of torture - Tran, Thien-Kim T (2019)
This thesis highlights how entertainment media perpetuates the public perception that the use of torture is an effective method to gain valuable and actionable intelligence from enemy combatants. This poses a significant problem to society because torture does not work, and if society continues to believe this misperception, it may lead to the erosion of societal morals for future generations. A possible explanation for entertainment media’s role in the continuation of this misperception could be related to the mere exposure effect due to frequency of torture being seen on television. In order to see how entertainment media perpetuates this misperception, three television shows, 24, Chicago P.D., and Homeland, were chosen to be screened for the presence of torture in episodes of the shows. For each randomly selected episode, indicators of torture and dialogue were monitored and recorded into a data set that marks the episode and time that the acts occurred. In addition to indicators of torture, the description of the individual being tortured was also recorded. After scanning a third of each show, 55% of the episodes in 24, 60% of the episodes in Chicago P.D., and 35% of the episodes of Homeland depicted torture. From these results, it is argued that it is likely these television shows made a significant impact on the public perception of the effectiveness of torture due to how often they were shown and because who was getting tortured